2011
DOI: 10.1097/aog.0b013e318214f0de
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Menopausal Hot Flushes and Associated Risk Factors

Abstract: OBJECTIVE To estimate the duration of moderate-to-severe menopausal hot flushes and identify potential risk factors for hot flush duration. METHODS The Penn Ovarian Aging Study cohort was followed for 13 years. Hot flushes were evaluated at 9-month to 12-month intervals through in-person interviews. The primary outcome was the duration of moderate to severe hot flushes, estimated by survival analysis (N=259). Potential risk factors included menopausal stage, age, race, reproductive hormone levels, body mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
130
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(151 citation statements)
references
References 50 publications
12
130
1
8
Order By: Relevance
“…Two studies that have looked at duration of vasomotor symptoms and associated risk factors (in naturally menopausal women) both found that lower education levels were associated with longer durations [27,28]. Obesity was also a risk factor, but in white women only [28]; this association was not seen in a multi-ethnic cohort [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies that have looked at duration of vasomotor symptoms and associated risk factors (in naturally menopausal women) both found that lower education levels were associated with longer durations [27,28]. Obesity was also a risk factor, but in white women only [28]; this association was not seen in a multi-ethnic cohort [27].…”
Section: Discussionmentioning
confidence: 99%
“…One of the strongest predictors of longer vasomotor symptom duration in studies of women who experienced natural menopause was if the symptoms began early in the menopause transition (premenopausal or perimenopausal) [27,28] . All of the women in our hysterectomy group had their surgery before they were 50 years old and likely to be in these early menopausal stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As menopause is characterized by declining estrogen levels, which may lead to the development of symptoms that include hot flashes, night sweats, vaginal dryness, mood swings, insomnia, lethargy/fatigue, and irritability 2 , this may explain the deterioration in women's sexual life as reported in other studies 7,24,25 . Another factor associated with women's self-classification of their sexual life as very poor, poor or fair was current or past use of natural remedies to treat menopausal symptoms (p=0.035).…”
Section: Discussionmentioning
confidence: 90%
“…Наконец, завершившееся в 2011 г. 13-летнее проспективное когортное исследование [8] уточнило медиану продол-жительности умеренно тяжелых и тяжелых приливов, которая составила 10,2 года, при-чем при включении в анализ лиц, испытыва-ющих легкие приливы, она возросла до 11,6 года. …”
unclassified